2017
DOI: 10.1038/s41598-017-02613-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort vortex from a Gaussian pulse – An achromatic-interferometric approach

Abstract: The more than a century old Sagnac interferometer is put to first of its kind use to generate an achromatic single-charge vortex equivalent to a Laguerre-Gaussian beam possessing orbital angular momentum (OAM). The interference of counter-propagating polychromatic Gaussian beams of beam waist ωλ with correlated linear phase (ϕ 0 ≥ 0.025 λ) and lateral shear (y 0 ≥ 0.05 ωλ) in orthogonal directions is shown to create a vortex phase distribution around the null interference. Using a wavelength-tunable continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…Amidst these methods, Atencia et al developed a compound holographic optical element to generate achromatic vortices [20], while Swartzlander designed achromatic spiral phase plates from two different glasses, providing a perfect topological charge at two wavelengths, akin to achromatic lenses [21]. who introduced an elegant approach based on a Sagnac interferometer to generate achromatic vortices [22], these techniques often prove complex or challenging to implement, and/or incompatible with the generation of high-energy ultra broadband vortex pulses. An alternative to generating a wide-band optical vortex directly (i.e., transforming a field without OAM), is to use an optical parametric chirped pulse amplifier (OPCPA) [23] to transfer the OAM of a narrowband pump beam to a wide-band idler beam.…”
mentioning
confidence: 99%
“…Amidst these methods, Atencia et al developed a compound holographic optical element to generate achromatic vortices [20], while Swartzlander designed achromatic spiral phase plates from two different glasses, providing a perfect topological charge at two wavelengths, akin to achromatic lenses [21]. who introduced an elegant approach based on a Sagnac interferometer to generate achromatic vortices [22], these techniques often prove complex or challenging to implement, and/or incompatible with the generation of high-energy ultra broadband vortex pulses. An alternative to generating a wide-band optical vortex directly (i.e., transforming a field without OAM), is to use an optical parametric chirped pulse amplifier (OPCPA) [23] to transfer the OAM of a narrowband pump beam to a wide-band idler beam.…”
mentioning
confidence: 99%
“…This system was based on tiled-aperture coherent beam combination where the VBs were generated by individually controlling the phase of each laser channel. Another approach is the interferometric generation of VBs directly inside a resonator [21]. The generation of up to 31 W of average power at a repetition rate of 600 kHz and at a wavelength of 1064 nm was demonstrated in a Q-switched laser with this scheme [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, limited reports are available on the generation of high-order tunable femtosecond vortices using active methods. Passive femtosecond vortex laser generators utilize the spiral phase plate [13,14], computer-generated hologram [15], axially symmetric polarizer/axially symmetric half-wave plate [16], uniaxial crystal [17], spiral grating [18], spiral multi-pinhole plate [19], Sagnac interferometer [20], and cylindrical lens pair [21][22][23]. It is reported that computer generated holograms and cylindrical lens mode converters can realize a high-order tunable femtosecond vortex laser.…”
Section: Introductionmentioning
confidence: 99%